The Use of Tiered Activity in Teaching Reading to Senior High School Students - Nirwana Ayu Maghfirah; Fitrawati Fitrawati (Journal of English Language Teaching, 2018)
Many of senior high school students face some problem in learning reading, for instance having difficulty in understanding the ideas of the text, limited vocabulary and the lack of motivation. The problems are caused by the lack of teaching reading strategy where the students are asked to do the same activity from limited learning materials in every meeting.  Thus, the writer chose Tiered Activity as a good strategy to be applied in the classroom. Tiered activity helps the students to be more motivated to comprehend the text by reading the text based on their reading ability levels, interest, and learning styles. There are three steps in tiered activity. First, readiness tier, the students are grouped based on their reading ability levels. Second, interest tier, the students will be grouped based on the text they are interested in. Third, learning style tier, the students will choose the text based on their learning style and perform the conclusion in front of the class. At the end of the lesson, the teacher and the students conclude the lesson together. Tiered activity is expected to increase the students reading ability and motivation in learning reading.